Psychological First Aid - Sanjay Kalra; Atul Dhingra; Kumar Abhisheka; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
In this communication, we discuss the concept of psychological first aid, as relevant to diabetes management. Psychological first aid, in the diabetes care context, is defined as “the empathic support, counselling and education to improve coping skills, and optimize selfcare of persons living with diabetes, so that psychological well-being can be optimized.” Various models can help provide structured psychological first aid. We feel that each and every health care provider should be able to provide effective first aid, including psychological first aid. Keywords: Diabetes, diabetes distress, insulin, person centred care, psychosocial Aspects